Implementation of PAI Learning through Problem Based Learning Methods to Improve Learning Achievement at SMP Karya Pembangunan Ciparay Bandung - Ai Sumarni; Badruzzaman; Hanafiah (CV. AFDIFAL MAJU BERKAH, 2022)
This research is based on the fact that teachers as managers for their students, in learning activities carried out in junior high schools generally still use conventional learning methods. This has an impact on student learning achievement. The purpose of education is stated in the National Education System Law no. 20 of 2003 can be achieved, the facts in the field of active, innovative, creative, effective and fun learning have not yet been implemented. The indicator is that there are students who are not active in discussions, lazy in solving problems. Seeing this phenomenon, it is necessary to take steps to overcome it with PAI learning management with Problem Based Learning (PBL) as an effort to improve learning achievement. The PBL method requires students to be active, creative, and cooperative in their learning, so they can apply it in real life. The purpose of this research is to describe the planning, implementation, assessment, supporting factors, obstacles and solutions. The methodology used is descriptive qualitative by collecting data through observation, interviews and documentation. The research process is determined by the subject, approach, type, location and research technique as well as testing the validity of the data and data analysis. The results of the research from the problems obtained are balanced with the achievements of class IX-A and IX-G, the learning achievement is still low, seen from the achievement of the score is not optimal. From the results of the assessment, the average value was not found below. Conclusion: Problem Based Learning method is able to improve learning achievement with indicators of cognitive, affective, and psychomotor values ​​exceeding the KKM.